HUBUNGAN PERILAKU MENYIKAT GIGI DAN TINGKAT PENGETAHUAN KEBERSIHAN GIGI DAN MULUT PADA SISWA KELAS V SDN 17 DAUH PURI TAHUN 2016 - Ni Wayan Arini; Ni Ketut Anggi Rismayanti (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
Oral health disorders will have an impact on one's performance. There are three factors that influence a person's behavior, namely predisposing factors, supporting factors, and reinforcing factors. Health behavior is divided into three namely, attitudes, actions and knowledge. Knowledge is a very important domain for the formation of one's actions. Ni Ketut Anggi Rismayanti's 2016 study at SDN 17 Dauh Puri Denpasar showed that most students had the ability to brush teeth quite as many as 24 people (58.53%) and 22 students (52.65%) had sufficient levels of dental and oral hygiene knowledge. . The purpose of this study was to determine the relationship of tooth brushing behavior with the level of dental and oral hygiene knowledge in fifth grade students of SDN 17 Dauh Puri Denpasar in 2016. This type of cross sectional study used secondary data from Ni Ketut Anggi Rismayanti's research. Spearmen correlation test between the variables of tooth brushing behavior with the level of dental and oral hygiene knowledge obtained sig. 0,000. Conclusion there is a relationship between variable brushing behavior with the level of dental and oral hygiene knowledge.